Does pharmacist-led medication review help to reduce hospital admissions and deaths in older people? A systematic review and meta-analysis - Holland, Richard (Blackwell Science Inc, 2008)
We set out to determine the effects of pharmacist-led medication review in older people by means of a systematic review and meta-analysis covering 11 electronic databases. Randomized controlled trials in any setting, concerning older people (mean age > 60 years), were considered, aimed at optimizing drug regimens and improving patient outcomes. Our primary outcome was emergency hospital admission (all cause). Secondary outcomes were mortality and numbers of drugs prescribed. We also recorded data on drug knowledge, adherence and adverse drug reactions. We retrieved 32 studies which fitted the inclusion criteria. Meta-analysis of 17 trials revealed no significant effect on all-cause admission, relative risk (RR) of 0.99 [95% confidence interval (CI) 0.87, 1.14, P = 0.92], with moderate heterogeneity (I(2) = 49.5, P = 0.01). Meta-analysis of mortality data from 22 trials found no significant benefit, with a RR of mortality of 0.96 (95% CI 0.82, 1.13, P = 0.62), with no heterogeneity (I(2) = 0%). Pharmacist-led medication review may slightly decrease numbers of drugs prescribed (weighted mean difference = −0.48, 95% CI −0.89, −0.07), but significant heterogeneity was found (I(2) = 85.9%, P < 0.001). Results for additional outcomes could not be pooled, but suggested that interventions could improve knowledge and adherence. Pharmacist-led medication review interventions do not have any effect on reducing mortality or hospital admission in older people, and can not be assumed to provide substantial clinical benefit. Such interventions may improve drug knowledge and adherence, but there are insufficient data to know whether quality of life is improved.